Analysis of the Effectiveness of 3D Printing Technology as an Alternative to Replacing Machine Components - Putra, Rama Dani Eka; Fitri, Tessa Zulenia (Journal of Engineering Science and Technology Management (JES-TM), 2024)
Three-dimensional printing (3D printing) technology has developed rapidly and offers innovative solutions in the manufacturing industry, especially for replacing damaged machine components. This research aims to analyze the perception and effectiveness of this technology as an alternative through empirical data from 300 respondents. The test results show that perceptions of 3D printing's ability to replace traditional components, the quality of the print results, and environmental benefits are significantly influenced by the respondent's level of experience (p-value < 0.05). However, aspects of cost efficiency and ease of application of technology show uniformity of perception across all groups of respondents, indicating the potential for broad application of technology. The normality and ANOVA tests performed confirmed the validity of the data, supporting the use of parametric statistical analysis. These findings underscore the ability of 3D printing to reduce costs and production time, while highlighting key challenges related to material strength and initial investment. This research recommends the development of materials, hardware, and ongoing education to increase the acceptance and effectiveness of the application of this technology in the manufacturing industry.